A preliminary analysis of base saturation flow rate during first loss time and saturated time at pretimed signalized intersections - Syahrul Fazila Teuku; Sugiarto Sugiarto; Saleh Sofyan M.; Rusdi Muhammad (E3S Web of Conferences, 2024)
Saturation flow rate is a key parameter essential for assessing signalized intersection capacity. The reference often used for signalized intersection planning in Indonesia is Indonesian Highway Capacity Guidelines (PKJI, 2023). In heterogeneous traffic environments, it has been observed that driver characteristics and behaviors exhibit significant variations. Therefore, this study aimed to investigate the prevailing saturation flow rate conditions at signalized intersections within Banda Aceh City. This exploration unfolded through two distinct scenarios, namely saturated time with and without initial lost time. For data acquisition, the focus was set on four signalized intersections, namely Jambo Tape, Pocut Baren, AMD Batoh, and Lhong Raya. This extraction procedure aimed to uncover insights into vehicle composition, movement patterns, and field saturation flow rate at these signalized intersections. In the aspect of analysis, a simple linear regression approach was adopted to recalibrate saturation flow rate coefficient of signalized intersections. This recalibration took into account vehicle compositions at the observation locations. The culmination of this analysis showed that in the scenario devoid of lost time under prevailing conditions, flow rate yielded S0 = 352 x Le. Meanwhile, for the scenario entailing lost time, the calculation produced was S0 = 294 x Le.